Hardware Removal after Osseous Free Flap Reconstruction - Day, Kristine E. (Otolaryngol Head Neck Surg, 2013)
OBJECTIVE: Identifying risk factors for hardware removal in patients undergoing mandibular reconstruction with vascularized osseous free flaps remains a challenge. The purpose of this study is to identify potential risk factors, including osteocutaneous radial forearm versus fibular flap, for need for removal and to describe the fate of implanted hardware. STUDY DESIGN: Case series with chart review. SETTING: Academic tertiary care medical center. SUBJECTS AND METHODS: Two hundred thirteen patients undergoing 227 vascularized osseous mandibular reconstructions between the years 2004 and 2012. Data were compiled through a manual chart review, and patients incurring hardware removals were identified. RESULTS: Thirty-four of 213 evaluable vascularized osseous free flaps (16%) underwent surgical removal of hardware. The average length of time to removal was 16.2 months (median 10 months), with the majority of removals occurring within the first year. Osteocutaneous radial forearm free flaps (OCRFFF) incurred a slightly higher percentage of hardware removals (9.9%) compared to fibula flaps (6.1%). Partial removal was performed in 8 of 34 cases, and approximately 38% of these required additional surgery for removal. CONCLUSION: Hardware removal was associated with continued tobacco use after mandibular reconstruction (P = .03). Removal of the supporting hardware most commonly occurs from infection or exposure in the first year. In the majority of cases the bone is well healed and the problem resolves with removal.